PENERAPAN METODE TECHNIQUE ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) UNTUK MENENTUKAN PESERTA DIDIK TERBAIK DI LPK FARAFI - Alfonsa, Rika Aprilinda; Saprudin, Usep (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2024)
Students are a group of people who try to develop their potential through the learning process available in certain learning stages, stages and categories. There are two categories of learning, namely Formal and Non-Formal Learning. LKP Farafi is a non-formal learning institution that is active in the field of computer courses, where every year there are students who take courses. To increase the students' enthusiasm for learning, LKP Farafi always gives prizes to students who have completed the course by determining the best students in each class group. The selection of the best students is carried out to determine prospective students who will receive prizes for their achievements. Currently the process for determining the best course students at LKP Farafi is still manual so it takes a long time to determine the best students. This research aims to select students who are more objective because they can be weighted against predetermined criteria using the Technique Order Preference By Similarity To Ideal Solution (TOPSIS) method. Using predetermined selection criteria, namely Character Assessment, Completion of Theory Assignments, Completion of Practical Assignments and Final Examination. The final results obtained are information on the best students who achieved the highest scores, starting from the best student 1 to the best student 3, which consists of 15 course participants in 1 class group.